Thermodynamics interactive multimedia to improve physics prospective teacher's generic science skills. Issue 3 (February 2019) - Hakim, A; Liliasari, L; Setiawan, A; Amir, M
Abstract: This study aimed to determine the increase of generic science skills (GSS) as result of the implementation of the interactive multimedia thermodynamics. Research method used a quasi experiment with control group pretest-posttest design. The research subject was 34 students as experimental group and 33 students as control group of physics prospective teachers of the fourth semester, in one of the state university in East Kalimantan. The research instrument used multiple choice test embeded GSS. Data analyzed with the differences of two averages. The result showed that after the implementation of interactive multimedia increased of GSS of physics prospective teachers quite effectively. The highest of normalized gain of GSS indicator of mathematical modeling (0.67), and the lowest for causality (0.53). These results indicated that the interactive multimedia increase the GSS of physics prospective teachers.